2006
DOI: 10.1681/asn.2005090954
|View full text |Cite
|
Sign up to set email alerts
|

Role of CXC Chemokine Receptor 3 Pathway in Renal Ischemic Injury

Abstract: I schemia-reperfusion (I/R) injury could lead to ischemic renal failure, which is one of the most common forms of acute renal failure of the native kidneys as well as of the renal allograft (1-5). Despite major advances in understanding the pathogenesis of I/R, no satisfactory therapy is available, and ischemic acute renal failure remains a major cause of morbidity and mortality (6). I/R injury begins with tissue hypoperfusion/hypoxia and leads to depletion of cellular ATP and cytoskeletal damage (7,8). Restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 49 publications
4
61
1
3
Order By: Relevance
“…The pathophysiological mechanisms of acute ischemic renal failure involve multiple mediators, such as proinflammatory cytokines, reactive oxygen species, adhesion molecules/chemokines, and the activation of leukocytes and endothelial cells that lead to tubular injury, endothelial dysfunction, and inflammation. [24][25][26][27] In the present study, IL-18 was observed to be upregulated in renal IRI.…”
Section: Discussionsupporting
confidence: 63%
“…The pathophysiological mechanisms of acute ischemic renal failure involve multiple mediators, such as proinflammatory cytokines, reactive oxygen species, adhesion molecules/chemokines, and the activation of leukocytes and endothelial cells that lead to tubular injury, endothelial dysfunction, and inflammation. [24][25][26][27] In the present study, IL-18 was observed to be upregulated in renal IRI.…”
Section: Discussionsupporting
confidence: 63%
“…Data from experimental models further support the functional importance of the CXCR3 receptor in T cell trafficking. Involvement of CXCR3 was reported in murine models of heart allograft rejection (36), autoimmune type 1 diabetes mellitus (37), and acute renal ischemic injury (38,39). CXCR3…”
Section: Discussionmentioning
confidence: 98%
“…At an early time point of renal IRI, we demonstrated an increase in the influx of CD4 ϩ T cells and NKT cells. Chemokines mediate leukocyte migration into the injured kidney and IFN-␥ modulates chemokine production, including IFN-␥-inducing protein 10 (IP-10), monokine-induced by IFN-␥, and IFN-␥-inducible T cell chemoattractant production, which bind to CXCR3 to mediate T cell migration (25) (25)(26)(27)(28)(29)(30). Our previous study showed that renal IRI up-regulated IP-10 and MIP␣, MIP1␤, MIP2, which are thought to mediate T cell and neutrophil migration (31,32).…”
Section: Discussionmentioning
confidence: 99%